The importance of thermoperiod for proper gametogenesis and successful egg and sperm production in meagre (Argyrosomus regius) breeders in aquaculture - Mello, Paulo H. de [UNESP]; Lancerotto, Stefano; Fakriadis, Ioannis; Tsoukali, Panagiota; Papadaki, Maria; Mylonas, Constantinos C. (Natl Centre Marine Research, 2021)
We examined the effect of constant water temperature throughout the year on gametogenesis, spawning success and egg/sperm/embryo quality in meagre (Argyrosomus regius). Two broodstocks were exposed to simulated natural photoperiod, and either attenuated seasonal water temperature (SeasT, 16.4 to 19.6 degrees C) or relatively constant water temperature (CoT, 19.4 +/- 0.6 degrees C). In the spawning period (May), 4 couples per group were induced to spawn with gonadotropin releasing hormone agonist (GnRHa). Gonadal stage of development, sperm quality parameters and plasma levels of sex steroids were evaluated prior to the GnRHa treatment. Spawning success and egg/sperm quality were examined over the following 4 weeks. Constant temperature did not prevent gametogenesis, but exposure to attenuated seasonal water temperature with the inclusion of winter low temperature was beneficial to both sexes. The mean (+/- SD) diameter of the largest vitellogenic oocytes prior to GnRHa administration was significantly higher in the SeasT compared to the CoT group (598 +/- 27 vs 520 +/- 17 mu m). Testosterone plasma levels in the females were significantly higher in the SeasT group, but all other hormones were similar in both sexes. SeasT females spawned more consistently with higher relative fecundity, and 24-h embryo survival of the produced eggs. A more pronounced negative effect of constant water temperature was observed in males, since CoT males exhibited a spermiation index of 0 prior to GnRHa treatment, the latter clearly having a beneficial effect over the following 4 weeks. The study demonstrated that meagre do undergo gametogenesis to a significant extent even under constant water temperatures during the year. However, a seasonal thermal regime -even an attenuated one- was necessary for the proper development of the gametes, allowing for the successful spawning induction using the established GnRHa induction protocol.
Keywords: Argyrosomus regius; GnRHa; spawning; temperature; gametogenesis; sperm quality